2021
DOI: 10.1007/s11002-021-09568-6
|View full text |Cite
|
Sign up to set email alerts
|

The cloud and its silver lining: negative and positive spillovers from automotive recalls

Abstract: Product recalls hurt the sales of non-recalled products in the category because of negative spillovers. Recently, there has been some evidence of positive spillovers from recalls on the sales of non-recalled products. We focus on spillovers from brand- (i.e., same brand), firm- (i.e., same firm, but not same brand), and country-level (i.e., same country-of-origin, but not same firm) recalls on the sales of non-recalled products. Furthermore, we examine how advertising and price of non-recalled products interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Such literature has shown that firms respond to a rival's bankruptcy by changing their product variety (Ren et al, 2019) and prices (Ozturk et al, 2016). Further, their sales can be affected by a rival's crisis (e.g., Giannetti & Srinivasan, 2021;Ozturk et al, 2019). We show that a firm's marketing investments prior to a rival's bankruptcy announcement also play a significant role in affecting investors' expectations of the firm's future prospects.…”
Section: Implications For Theory and Practicementioning
confidence: 80%
“…Such literature has shown that firms respond to a rival's bankruptcy by changing their product variety (Ren et al, 2019) and prices (Ozturk et al, 2016). Further, their sales can be affected by a rival's crisis (e.g., Giannetti & Srinivasan, 2021;Ozturk et al, 2019). We show that a firm's marketing investments prior to a rival's bankruptcy announcement also play a significant role in affecting investors' expectations of the firm's future prospects.…”
Section: Implications For Theory and Practicementioning
confidence: 80%
“…Second, various other aspects connected to the product might be affected by such claims, and the influence could even transcend the boundaries of the particular product. Prior research has indicated that marketing actions directed at one product, such as marketing communications or product recalls, may have implications not only for other products within the same brand or products from different brands within the same category (Balachander & Ghose, 2003; Chae et al, 2017) but also for different products originating from the same country (Giannetti & Srinivasan, 2021; Han, 1989). This implies that the negative effects of pseudo‐relevant 100% could potentially spill over and influence consumers' reactions to associated products and unrelated ones originating from the same country.…”
Section: Discussionmentioning
confidence: 99%